CHARACTERIZATION OF NOTCH FATIGUE CRACK INITIATION AND PROPAGATION OF INDUSTRIAL PURE TITANIUM BASED ON DIC - BAO QiLe; DAI Qiao; QIU Rui (Jixie qiangdu)
The fatigue test of industrial pure titanium notched specimens was carried out.Combined with digital image correlation(DIC)technology,the surface strain field of the specimen,the local strain at the notch root,and the fatigue crack propagation length were obtained,and the fatigue crack initiation and propagation stages were divided and characterized.The experimental results show that,in the fatigue crack initiation stage,the strain concentration factor obtained by DIC increases as the notch radius decreases,which is consistent with the theoretical stress concentration factor.When the cyclic strain at the notch root accumulates to a certain extent,the micro-cracks initiate.At this time,the increase of load causes the local strain rate to increase sharply,then decrease briefly and increases again until the appearance of macro-cracks.When macro-cracks appear,the fatigue crack propagation of TA2 is characterized by the stress intensity factor,which increases with the increase of load and crack length.The results show that the notch fatigue crack initiation and propagation can be characterized based on DIC technology,which can provide a basis for the safety assessment of titanium equipments.